2022-RA-1008-ESGO The impact of cytoreductive surgery in FIGO IV and recurrent endometrial cancer. (20th October 2022) - Natalia Strojna, Aleksandra; Ataseven, Beyhan; Heitz, Florian; Concin, Nicole; Moubarak, Malak; Westermann, Timo; Kaiser, Sabrina; Pauly, Nina; Dagres, Timoleon; Vrentas, Vasileios; du Bois, Andreas; Traut, Alexander; et al.
Abstract : Introduction/Background: The aim of the study was to assess the oncological outcomes of cytoreductive surgery in FIGO IV and recurrent endometrial cancer. Methodology: This is a retrospective, observational, single-center cohort study including patients with endometrial cancer FIGO IV stage disease undergoing primary cytoreductive surgery and recurrent endometrial cancer treated with secondary cytoreductive surgery between January 1999 and April 2022. Results: 115 patients were included in the present study. In the 53 patients with primary FIGO IV disease complete macroscopic resection was achieved in 42/53 (79.2%) cases. Median OS in these patients was 35 months and median PFS was 15 months. Sixty-two patients had cytoreductive surgery for relapsed endometrial cancer and complete macroscopic resection was achieved in 82.2%. Median OS in this population was 28 months and median PFS was 8.2 months. Patients with complete macroscopic resection showed longer progression-free survival (PFS) and overall survival (OS) compared to those with residual disease (PFS: 15.1 vs 12.9 months; p=0, 189; OS: 32.4 vs 17 months; p=0, 130). Median OS was 44.6 months (95 % CI 24, 6- 64, 6 months) in endometrioid subtype (72/115 pts) and 27.4 months (95 %CI 7.2–47.6 months) in other histotypes (p=0.114). Major complications (>Clavien Dindo IIIB) were noted in 10/115 pts (8.7%), mortality rate was 0.9%. Conclusion: Complete macroscopic resection is feasible in selected patients with FIGO IV and relapsed endometrial cancer with an acceptable morbidity, and seemed to be related to superior outcome. However, its impact on prognosis should be further evaluated.